Relasi Bapa dan Putra sebagai Model Relasi Kita dengan Kristus: Suatu Komentar atas Tujuh Tesis Ratzinger tentang Doa Yesus - WICAKSONO, AGUNG (Lux et Sal, 2021)
Within Christianity the purpose of spiritual life lies in the glory of God and the sanctification of mankind. It all boils down to a deep union between God and man. The path taken to achieve this is prayer, because, in and through prayer, man becomes honest with himself. No pretense there. Prayer involves one's entire being. In this paper, Jesus' prayer is chosen as a basis and model in establishing oneness with God. The author will set out and comment on Joseph Ratzinger's thoughts on the Jesus prayer in seven basic theses.